Interfacial bond properties between polypropylene fiber mortar and rock with different roughness - Jianliang Hu; Yunchao Huang; Xiuru Wang; Yuhui Liu; Shihui Yu; Shizhao Shen; Weijie Pan; Sheng Chen; Yunshan Shen (Materials Research Express)
Effective reinforcement measures for the surrounding rock of the tunnel are crucial to ensure the safety of tunnel engineering. Fibers are very effective in improving the quality of the interface; however, to promote the application of fiber mortar (FM) in tunnel lining reinforcement, it is necessary to study the bonding performance between FM and rock. The mechanical properties of ordinary mortar (OM) and FM were investigated, and bonding performance tests were conducted. The effect of polypropylene (PP) fibers on the mechanical properties and the influence of PP fibers and surface with different roughness on the bond properties were analyzed in detail. A 3D printer was used to print various structural boards to characterize different roughness levels, and the shape of the printed model was effectively controlled, thereby ensuring the consistency and repeatability of the structural board. The test results indicated that the splitting tensile strength and volumetric strain of the mortar were improved significantly with the addition of PP fibers, in which the splitting tensile strength increased by 38%, the elastic modulus and Poisson’s ratio increased, and the deformation and energy absorption capacity were enhanced; however, there was little effect on its compressive strength. The bonding performance between mortar and rock surface were enhanced with the increase in roughness, and the direct shear strength recorded the highest value while the bond specimens with a surface roughness of joint roughness coefficient 18–20, also the PP fibers improved the bond properties. This study will be helpful for promoting the application of FM in tunnel surface lining engineering.